1986
DOI: 10.1111/j.1471-6402.1986.tb00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Personality Attributes and Reaction to Success/Failure: An Examination of Mediating Variables

Abstract: The effects of success and failure on task performance, and attributions about performance, were compared for high and low instrumental college women. For the+high instrumental group, success facilitated task performance, whereas f a~~~~a~~ o effect on sXSqTerperformance, ITg7;rnstrumentaI women attributed w instrumental women revealed the opposite profile. The gender-appropriateness of the task had little effect on performance or attribution. Four potential mediators of these differences were investigated: se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These variables included locus of standards, initial expectations, process versus outcome focus, and the overall time frame of the event. The relevance of these features of achievement has been firmly established (Atkinson, Nicholls, 1975;Veroff, 1977; Welch, Gerrard, & Huston, 1986). However, this relevance has been documented primarily in the context of traditional forms of achievement.…”
Section: Studymentioning
confidence: 99%
“…These variables included locus of standards, initial expectations, process versus outcome focus, and the overall time frame of the event. The relevance of these features of achievement has been firmly established (Atkinson, Nicholls, 1975;Veroff, 1977; Welch, Gerrard, & Huston, 1986). However, this relevance has been documented primarily in the context of traditional forms of achievement.…”
Section: Studymentioning
confidence: 99%
“…Working toward instrumental autonomy can provide many benefits for women. Welch, Gerrard, and Huston (1986) found that women who score high on instrumental personality attributes (active, independent, competitive) improved their performance after success, did not deteriorate after failure, and were better able to attribute success to ability and failure to external causes. "High instrumental women" had higher perceived ability, expectancies of success, and self-esteem than did "low instrumental women."…”
Section: Instrumental Autonomymentioning
confidence: 99%
“…Baruch et al (1983) found the concept of mastery (doing and achieving) to be related to well-being in women. Welch et al (1986) suggested that low instrumental women respond to failure by attributing it to poor ability; thus, they respond quickly to failure by assuming they cannot perform a task. Jones and Lamke (1985) found that women with androgynous and masculine (instrumental) gender role orientations had higher levels of self-esteem than did women with more feminine (expressive) and undifferiented gender role orientations.…”
Section: Instrumental Autonomymentioning
confidence: 99%